The impact of implementation of change management processes on staff turnover : a case of Zimbabwe telecommunications industry - Mutesva, Gladmore (Midlands State University, 2020)
Telecommunications companies, over the last decade, have undergone major change in terms of the manner in which they do business. The objective of this study was to investigate the impact of change implementation on staff turnover in telecommunications industry by reviewing the following key issues, the effect of change implementation on staff turnover, the implementation of change within the industry, the communication of change initiatives by management in the industry, and the effect of change implementation on employee morale and retention. The rationale of this study was to allow top executives to review their current implementation strategy of change management initiatives in the industry. Thereafter, it provided guidelines for improvements in change implementation for the leaders. Staff turnover can negatively impact service delivery and financial performance of a company, so these recommendations are aimed at improving change management initiatives. The study was descriptive and quantitative in nature, involving the application of a questionnaire, with a sample of staff from all departments in the industry. The questionnaire focused on assessing the impact of the implementation of change management processes on staff turnover in the telecommunications industry and was developed from the literature review. Data was analyzed using the Statistical Package for the Social Sciences (SPSS), Version 24 for both descriptive and inferential statistics. The findings show that a significant percentage of respondents were in disagreement with the way management had handled issues related to change implementation, turnover, communication, retention and morale. With this in mind, recommendations on ways to reduce the impact of the key issues on the organization were made. These included the recommendation of lean methodology in order to deal with the first three key issues, namely, communication, implementation, and turnover. Finally, recommendations were made on ways to improve employee retention. The primary issue that has come to light is that although management is, to a certain extent, communicating change implementation, there is a noticeable lack of engagement with employees. The onus, therefore, lies with leadership to lift the levels of engagement with employees, thereby reducing the impact of change implementation on the organization by increasing the level of transparency in the organization. Improving communication would lead to improved trust, which would then result in improved employee morale, ultimately leading to a reduction in the staff turnover rate.